1981
DOI: 10.1161/01.cir.63.3.565
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete mitral leaflet closure in patients with papillary muscle dysfunction.

Abstract: SUMMARY Clinical acceptance of an association between papillary muscle dysfunction and mitral regurgitation is widespread, despite the lack of objective support. To evaluate a possible association, we performed echocardiographic examinations on 22 patients with prior myocardial infarction and clinical evidence of papillary muscle dysfunction, 40 patients with prior myocardial infarction and no clinical evidence of papillary muscle dysfunction, and 20 normal subjects. There was a unique pattern of incomplete mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
126
0
9

Year Published

1983
1983
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(138 citation statements)
references
References 12 publications
3
126
0
9
Order By: Relevance
“…Previous clinical [15][16][17] and experimental 8,18,19 studies have described the role of papillary muscle displacement in the development in CIMR. Other investigators have used echocardiography to link both total and laterally-directed papillary muscle displacement to apical restriction of the mitral leaflets.…”
Section: Papillary Muscle Geometrymentioning
confidence: 99%
“…Previous clinical [15][16][17] and experimental 8,18,19 studies have described the role of papillary muscle displacement in the development in CIMR. Other investigators have used echocardiography to link both total and laterally-directed papillary muscle displacement to apical restriction of the mitral leaflets.…”
Section: Papillary Muscle Geometrymentioning
confidence: 99%
“…The degree of MR did not differ between treatment groups (ERV mean MR grade 1.4Ϯ0.9 versus IMS 1.3Ϯ0.9). Apical displacement of mitral leaflet coaptation, also known as incomplete mitral leaflet closure pattern, 16 was noted in 40% of those with grade 2ϩ to 4ϩ MR.…”
Section: Cardiac Structure and Function In Acute Cardiogenic Shockmentioning
confidence: 99%
“…Ischaemic MR results from complex alterations of spatial relationships between the LV and mitral apparatus 23 and a recent study confirmed that MR severity is related to systolic tenting and not LV dysfunction 24 . Ischaemic MR occurring early or late after AMI is associated with increased mortality 25 , 26 , and severe MR portends poor prognosis 27 , 28 . Transthoracic echocardiography (TTE) enables analysis of the mechanism and severity of MR, and transoesophageal echocardiogram (TOE) is only occasionally necessary.…”
Section: Traditional Measurementsmentioning
confidence: 99%